Strategic Financial Management: Maximizing Value and Minimizing Risk in a Dynamic Global Marketplace - Sajad M. & Ali Abd AlUhssein (International Journal of Innovative and Applied Finance, 2023)
login and register and pay the fees to get an open access to content